A discussion of some controversies in mixed methods research for emerging researchers - Joseph Adu; Mark Fordjour Owusu; Ebenezer Martin-Yeboah; Lisbeth Alexandra Pino Gavidia; Sebastian Gyamfi (Methodological Innovations, 2022)
Mixed methods research has become an important approach to research worldwide. The combination of qualitative and quantitative research methods has made it possible for a deeper and broader understanding of multifaceted phenomena, thereby offering readers more confidence in research findings and conclusions. The use of mixed method designs became more established in the 1980s and early 1990s, but some controversies surrounding the approach remain. Nonetheless, experts in the field of mixed methods research have continued to work on the central premise that the use of qualitative and quantitative approaches, in combination, provides a better understanding of research problems than either approach alone. This concept paper discusses some of the known controversies around mixed methods with the aim of providing useful insights to emerging researchers interested in learning the methodology.